DIFFERENT POLYMORPHISMS OF PLACENTAL GROWTH FACTOR (PLGF) GENE IN IRANIAN WOMEN'S POPULATION WITH PRE-ECLAMPSIA - Pourroostaei Ardakani, Parisa; Ramezani, Arezoo; Piravar, Zeinab; Asgharimoghadam, Nastaran; Behzadi, Roudabeh; Jafari Fesharaki, Mehrdad (International Journal of Cardiovascular Practice)
Introduction: Preeclampsia is a complication affecting pregnant women worldwide, which leads to maternal and fetal morbidity and mortality. Due to the importance of mutations in the PLGF (Placental Growth Factor) gene and the association with the incidence of preeclampsia, this study aimed to evaluate the association of polymorphisms of the PLGF gene with the prevalence of preeclampsia in Iranian women.Methods: Fifty pregnant women with pre-eclampsia diagnosis and 50 healthy pregnant women for determination of genotypes rs1464547123, rs12411, rs1399853427, and rs1312670436 were evaluated using the Sanger sequencing method.Results: There was no significant difference in the frequency of alleles ofrs1464547123, rs1399853427 and rs1312670436 polymorphisms between case and control groups (P > 0.05), but the rate of recessive allele A in rs12411 polymorphism was significantly higher in the case group than in the control group (case = 24%, control = 8%, P-Value = 0.04), while the frequency of the allele T in the control group was higher than that of the patient group (case = 76%, control = 92%, P-Value = 0.04) The frequency of AT genotype in the patient group was a none significantly higher than the control group (case = 8%, control = 4%, P-Value = 0.1) and the frequency of AA genotypes in the case group was none significantly higher than that of the control group (case = 16%, control = 4%, P-Value = 0.1).Conclusions: The results revealed that polymorphism rs12411 of the gene encoding PLGF has a significant difference among individuals with and without pre-eclampsia and can affect the incidence of pre-eclampsia among Iranian women.